Beyond the human body: Claire Denis's ecologies - Laura McMahon (Alphaville: Journal of Film and Screen Media, 2014)
This article explores the work of Claire Denis beyond the focus on the human body through which it is commonly read. Addressing Beau Travail (1999) and The Intruder (2004), I examine an ecological impulse that manifests itself through a nonanthropocentric detailing of the coexistence of body and landscape, and a nonhierarchical attentiveness to the distributed agencies of humans, animals and things. I draw here in particular on Gilles Deleuze’s notion of the crystal-image and on Jean-Luc Nancy’s thinking of ecotechnics, as elaborated in his essay on The Intruder (a film inspired by Nancy’s autobiographical essay, L’Intrus). In Beau Travail, Deleuzian crystals of time draw attention to the nonhuman histories of the landscape. In The Intruder, this crystalline structure persists, reactivating traces of nonhuman pasts, while a focus on canine gestures and responses signals nonhuman perceptual worlds in the present. Deleuze’s “Desert Islands”, another text that shapes The Intruder, offers a further way of reading the film’s attentiveness to the nonhuman—an attentiveness that extends, as Nancy suggests, to a consideration of environmental crisis.